Adsorption Of Phenolic Compunds Onto Granular Activated Carbon:Isotherms And Braekthrough Curves - Kiung, Ming Ming (2004)
Continuous fixed bed study and batch adsorption study were carried out by using NORIT Granular Activated Carbon 1240 (GAC) as an adsorbent for the removal of phenol, O-Cresol and 4-chlorophenol from aqueous solution